Desvelando identidades: a identidade profissional dos professores de língua portuguesa pertencentes ao programa de educação integral da rede pública estadual de Pernambuco - Albuquerque Júnior, Agenor Facundes de (2017)
This research aims to analyze the speeches of the Portuguese language teachers belonging to the Integral Education Program of the State Public Network of Pernambuco, on the light of Discourse Analysis of French Tradition (AD). Initially, we discussed the history of teaching work in Brazil, where we briefly tried to understand the continuities and ruptures of teaching performance and professionalization in Brazil. Then we put our conception of identity and teaching identity, determining the theoretical aspects that based our studies. We also highlight the process of professional teacher training that we consider essential to understand the process of teacher identity formation. We also seek to establish our understanding of integral education and the implementation of the Integral Education Program of the State Public Network of Pernambuco. We then set out our methodological assumptions, explaining our choice for a qualitative approach, our position on action research, and the need for an interventional approach, our choice of the Foucaultian archaeological approach, and our preference for the wheels of conversation. Finally, we describe our meetings through the wheels of conversation in order to guarantee spaces for dialogue, giving time and voice to the teachers. When analyzing the teaching discourses present in our rounds, we sought to identify the elements and characteristics responsible for the construction of their identities as teachers. Thus, our work seeks to contribute with the set of knowledge and strategies that guarantee recognition and empowerment as a subject and as a teaching professional.